Geomechanical model for surface excavation in tropically weathered granite - Khalil Abad, Seyed Vahid Alavi Nezhad (2014)
Mass heterogeneity, abrupt changes in weathering state and presence of boulders in tropically weathered granite lead to uncertainties in predicting the surface excavation performance. This study proposed a new geomechanical model for prediction of surface excavation rate by considering the complex characteristics and effective parameters of weathered granite. Beside the new model, a typical mass weathering profile of granite was proposed with details of rock mass characteristics including typical appearance, discontinuities characteristics, shape and size of boulder, homogeneity and rock to soil ratio in each mass weathering grade. Based on extensive study of fourty panels from four granite quarries, the effect of weathering on the mentioned parameters were established. Practical excavation was performed in excavable zones in the quarries. Statistical analysis using multiply linear regression was performed on the relation of the parameters and practical excavation rate to investigate effective parameters of rock mass and rock material in surface excavation. Then after, the correlation of each parameter with practical excavation rate was obtain utilizing Pearson Correlation Coefficient (PCC). Based on PCC and the results of laboratory tests and site investigation, a rating system in a chart know as Excavation Index in Granite (EIG) was proposed. EIG value was calculated for each weathering zone in each panel of the quarries. The correlation between the results of practical excavation and the values of EIG was obtain and then used to propose a chart of excavability classification in granite. The chart consists of excavation classes, the range of excavation rates and the excavability conditions. Finally, the applicability of the proposed model was verified by comparing the predicted ranges of surface excavation rate using the model and the results of practical excavation rate at another site. The proposed model contributes to the field of surface excavation in tropically weathered granite.